CORAK PENAFSIRAN ISYARI DALAM TAFSIR JEMA'AT AHMADIYAH QADIYAN (Satu Analisa dalam Perspektif Ilmu Tafsir) - Andi Putra Ishak (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2016)
Ahmadiyah Qadiyan interpretation controversy has caused tremendous reaction from Muslims around the world, not only in his native land claimed as the Ahmadis non-Muslim minority, even in the Islamic world is considered heretical groups in and out of Islam. This fallacy stems from religious interpretations that do not comply with the disciplines of Islam, giving rise to different views in terms of religious principles. However, Ahmadiyah still claiming to be performer true religion of Islam, because in principle they still cling to the Qur'an and other Islamic scientific sources such as tradition, the views of prophet Muhammad companions and his followers. In addition they also have their own interpretation book is "THE HOLY QURAN ARABIC TEXT WITH ENGLISH TRANSLATION & SHORT COMMENTARY". Bayiruddin Mahmud Ahmad, the Ahmadiyya Caliph as the author of the commentary has made this interpretation tends to isyari patterns that seem to justify the prophetic claims of Ghulam Ahmad, by because it is necessary Overview of disciplines commentators to see the extent of the validity of the interpretation.